Dinámica familiar y comisión de infracción penal por adolescentes beneficiarios de la Corte Superior de Justicia de La Libertad - Pinillos Caballero, Denitze Olenka (2019)
This investigation was prepared to publicize the factors of family dynamics that influence the commission of criminal offense by adolescents of the Superior Court of Liberty. This research is of a qualitative type, using the phenomenological method, using techniques such as interview and observation; the sample with which it was worked was 10 cases of adolescents who carry out processes for criminal infraction, in the multidisciplinary team of the Superior Court of Liberty Justice. The variables on which the research focused were the composition of family structure, communication and family cohesion, present in family dynamics. The conclusions reached were that the composition of the family structure of the offending adolescents presents single-parent families led by the mother and reconstituted families; regarding family communication, present in the families of adolescents, there is the type of passive communication because they describe their communication as regular, do not share their feelings and concerns and / or problems with their parents, and receive confusing messages; and aggressive communication in the presence of family discussions, shouts and reproaches; and finally in the cohesion levels, the mostly separated and disintegrated levels are presented.